The night the new Jesus fell to Earth : and other stories from Cliffside, North Carolina - Rash, Ron, 1953- (Southern revivals, 2014)
"The Night the New Jesus Fell to Earth was originally released in 1994 and was the first published book from acclaimed writer Ron Rash. This twentieth anniversary edition takes us back to where it all began with ten linked short stories, framed like a novel, introducing us to a trio of memorable narrators--Tracy, Randy, and Vincent--making their way against the hardscrabble backdrop of the North Carolina foothills. With a comedic touch that may surprise readers familiar only with Rash's later, darker fiction, these earnest tales reveal the hard lessons of good whiskey, bad marriages, weak foundations, familial legacies, questionable religious observances, and the dubious merits of possum breeding, as well as the hard-won reconciliations with self, others, and home that can only be garnered in good time. The Night the New Jesus Fell to Earth shows us the promising beginnings of a master storyteller honing his craft and contributing from the start to the fine traditions of southern fiction and lore. This Southern Revivals edition includes a new introduction from the author and a contextualizing preface from series editor Robert H. Brinkmeyer, director of the University of South Carolina Institute for Southern Studies"--